Lightweight Augmented Reality Tools for Lean Procedures in Future Factories - Capozzi, Francesco; Lorizzo, Valerio; Modoni, Gianfranco; Sacco, Marco (Augmented and Virtual Reality, 2014)
The aim of this paper is to introduce the main outcomes of the application of Augmented Reality (AR) features to manufacturing and industrial scenarios under a new perspective. While the request of industrial mixed reality technologies is continuously growing, the research community is still facing the crucial challenge to give a convenient answer to such needs. The problem of the development of adaptable and inexpensive AR solutions is herein addressed by proposing a new approach for the application of AR technology to lean-based visual communication transfer and exchange. This work starts from the concept of virtual factory, a place where the real production of future factories becomes fully merged with virtual reality features and utilities. AR applications may then be reinterpreted as lightweight tools that continuously interact with the virtual factory to support manufacturing and management tasks, providing just-in-time and adaptive augmented information to users. As a case study, several AR tools designed following these principles to support a real production process are presented.